Design and analysis of 5 kW helium turbine for EAST cryoplant. Issue 1 (1st May 2022) - Chen, S X; Zhang, Q Y; Fu, B; Li, S S; Fan, C F; Zhang, C J; Zong, Y W
Abstract: The helium turbine is an important core component in the refrigerator, which provides support and guarantee for the stable operation of the cryogenic system. This paper refers to the parameters of one of the four helium turbines in EAST, designs a 5 kW helium turbine. The overall structure of the turbine has been described, and the design and analysis of the impeller and bearing have been carried out. Through CFD analysis, the internal pressure and temperature change law of the flow is analyzed. The variable-condition operating characteristics of the turbine are predicted, and it is found that the turbine can maintain efficient operation within a wide range of mass flow changes. The bearing performance is calculated by solving the Reynolds equation. After determining the optimal bearing clearance 28 μm based on the principle of maximum stiffness, bearing performance parameters of load capacity and stiffness can be further calculated.